Technologies of stage magic: Simulation and dissimulation. (June 2015) - Smith, Wally
The craft of stage magic is presented in this article as a site to study the interplay of people and technology. The focus is on conjuring in the 19th and early 20th centuries, a time when magicians eagerly appropriated new optical, mechanical and electrical technologies into their acts. Also at this time, a modern style of conjuring emerged, characterized by minimal apparatus and a natural manner of performance. Applying Lucy Suchman's perspective of human-machine reconfigurations, conjuring in this modern style is interpreted as an early form of simulation, coupled with techniques of dissimulation. Magicians simulated the presence of supernational agency for public audiences, while dissimulating the underlying methods and mechanisms. Dissimulation implies that the secret inner workings of apparatus were not simply concealed but were rendered absent. This, in turn, obscured the production of supernatural effects in the translation of agencies within an assembly of performers, assistants, apparatus, apparatus-builders, and so on. How this was achieved is investigated through an analysis of key instructional texts written by and for magicians working in the modern style. Techniques of dissimulation are identified in the design of apparatus for three stage illusions, and in the new naturalness of the performer's manner. To explore the significance of this picture of stage magic, and its reliance on techniques of dissimulation, a parallel is drawn between conjuring and recent performances of computerized life forms, especially those of social robotics. The paper concludes by considering what is revealed about the production of agency in stage magic's peculiar human-machine assemblies.